2023
DOI: 10.1287/mnsc.2022.4390
|View full text |Cite
|
Sign up to set email alerts
|

Managing Relationships Between Restaurants and Food Delivery Platforms: Conflict, Contracts, and Coordination

Abstract: Restaurant delivery platforms collect customer orders via the Internet, transmit them to restaurants, and deliver the orders to customers. They provide value to restaurants by expanding their markets, but critics claim they destroy restaurant profits by taking a percentage of revenues and generating congestion that negatively impacts dine-in customers. We consider these tensions using a model of a restaurant as a congested service system. We find that the predominant industry contract, in which the platform ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 12 publications
0
28
0
Order By: Relevance
“…(2022) and Feldman et al. (2023) extend Naor's framework to consider a decentralized service setting similar to ours (e.g., a restaurant and a food delivery platform). They study the incentive issues between decentralized players in serving a market of heterogeneous customers.…”
Section: Literature Reviewmentioning
confidence: 95%
See 1 more Smart Citation
“…(2022) and Feldman et al. (2023) extend Naor's framework to consider a decentralized service setting similar to ours (e.g., a restaurant and a food delivery platform). They study the incentive issues between decentralized players in serving a market of heterogeneous customers.…”
Section: Literature Reviewmentioning
confidence: 95%
“…For amateur customers, their joining decisions also depend on the intermediary's fee decision. As the main goal of this paper is to understand how a provider of a complex professional service should treat various customer segments differentially on pricing and prioritization, we abstract away the contracting issues between the provider and intermediary (see Feldman et al., 2023 and Chen et al., 2022 for a relevant discussion) and focus on a simple setting in which the intermediary generates revenues by charging amateur customers a separate fee. We present a detailed formulation of the intermediary's fee decision and amateur customers' joining decisions in Subsection 3.2.…”
Section: Modelmentioning
confidence: 99%
“…In a crowdfunding context, Zhang et al (2017) study how the dynamics of the pledging process affect the optimal pledging level and campaign duration; Chakraborty and Swinney (2021) consider whether entrepreneurs can signal the quality of their product through their choice of crowdfunding campaign parameters; and Babich et al (2020) study how crowdfunding interacts with more traditional financing sources such as venture capital and bank financing. Feldman et al (2021) consider whether food-delivery platforms benefit restaurants. Kanoria and Saban (2021) show that search inefficiencies in matching markets can be alleviated by placing restrictions on agents' actions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They showed that only one platform can result in a "payoff dominant stable equilibrium" who will take all the benefit. Feldman et al (2022) explored a congested service system of the restaurant and analytically analyzed the supply chain performance under the commonly seen simple revenue-sharing contract in a supply chain with one restaurant and one thirdparty delivery platform. They concluded that a simple revenue-sharing contract is inefficient to coordinate the supply chain and harms the profitability of the restaurant.…”
Section: Operational Strategies and Performancesmentioning
confidence: 99%
“…Economic sustainability is a crucial dimension in triple bottom line (TBL) framework as the business firms have to be profitable for survival in the competitive marketplace. In the existing literature, two articles analytically examined the supply chain performance under the revenue-sharing contract and proposed the mechanism to achieve supply chain coordination Feldman et al, 2022). In real-world observation, we have found that third-party food delivery platform offers new subsidy scheme to restaurants to lessen their financial burden on the commission fee.…”
Section: Triple Bottom Line (Tbl)mentioning
confidence: 99%